CONFUSING BRAINS WITH RETURNS: EVIDENCE OF INVESTOR OVERCONFIDENCE AND TRADING ACTIVITY IN THE INDONESIAN STOCK MARKET - Yanuar Dananjaya; Hananiel Menoverdi; Priskila Napitupulu (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2026)
This study investigates the presence of investor overconfidence in the Indonesian equity market by analyzing the lead-lag relationship between stock returns and subsequent trading activity. Focusing on the constituents of the LQ45 index from January 2023 to December 2025, we employ a firm-level panel data approach with fixed effects and clustered robust standard errors on a monthly dataset (N=1,485$). Using share turnover as a proxy for trading intensity, the analysis tests the hypothesis that past positive returns lead to increased trading volume due to biased self-attribution. The empirical results demonstrate that both contemporaneous and lagged individual stock returns exert a positive and statistically significant influence on trading activity (p < 0.05$), confirming that Indonesian investors tend to trade more aggressively following periods of capital gains. This behavioral pattern remains robust across alternative turnover specifications, including total-share and free-float-based proxies, as well as log-transformed models. Furthermore, lagged market returns exhibit a dominant positive effect, suggesting that market-wide sentiment acts as a powerful catalyst for trading frequency. These findings provide strong evidence of overconfidence-driven behavior in the Jakarta Composite Index, highlighting how psychological biases—rather than purely fundamental information—drive market liquidity and volatility in an emerging market context.